Species diversity, distribution patterns, and substrate specificity of Strobilurus. (4th May 2018) - Qin, Jiao; Horak, Egon; Popa, Flavius; Rexer, Karl-Heinz; Kost, Gerhard; Li, Fang; Yang, Zhu L.
ABSTRACT: The fungal genus Strobilurus belongs to Physalacriaceae and contains approximately 11 species worldwide. Species of this genus grow and reproduce on cones of various conifers, seed pods or fruits of Magnolia and Liquidambar, and branches and wood of conifers. Previous studies focused mainly on samples from Europe and North America. And no genus-specific phylogenetic analysis has been carried out to date. The monophyly, degree of species diversity and substrate specificity, and overall distribution patterns are addressed here using morphological and molecular evidence. The authors collected samples of Strobilurus from much of its known distribution ranges and carried out morphological observations and multilocus phylogenetic analyses using five molecular markers. The results show that Strobilurus is a monophyletic group but may exclude one species, S. ohshimae . A total of 13 species was identified, with two, S. orientalis and S. pachycystidiatus, described as new from China. Several species were shown to be specific to certain substrates, whereas a few less so. Biogeographic analyses indicated that historical exchanges of species between East Asia, Europe, and North America, later vicariance events, and substrate specificity have contributed jointly to diversification of Strobilurus .